Rhodiosin and herbacetin in Rhodiola rosea preparations: additional markers for quality control? - Zoltán Péter Zomborszki; Norbert Kúsz; Dezső Csupor; Wieland Peschel (Taylor & Francis Group, 2019)
Context: Rhodiola rosea L. (Crassulaceae) is well-known to contain flavonoids such as the herbacetin derivative rhodiosin. However, flavonoids are not typically used in quality control. Objective: This study analyses two flavonoids of R. rosea rhizomes and roots for their potential as analytical markers. Materials and methods: Two constituents were isolated from ethanolic extracts via HPLC, identified via NMR and quantified via RP-HPLC. Presence and content variation was investigated according to extraction (solvent and repetitions), drying (temperature and duration) and sample origin (homogenously cultivated plants of different provenance, commercial samples). Results: Rhodiosin was identified as a main flavonoid, accompanied by 10-fold lower concentrated herbacetin. Both compounds were best extracted with 70-90% ethanol, but were also detectable in more aqueous extracts. Different drying conditions had no effect on the flavonoid content. These two flavonoids were consistently identified in rhizome and root extracts of over 100 R. rosea samples. Rhizomes tend to contain less flavonoids, with average ratios of rosavins to flavonoids of 1.4 (rhizomes) and 0.4 (roots). Provenance differences were detected in the range (rhodiosin plus herbacetin) of 760-6300 µg/mL extract corresponding to a maximum of approximately 0.5-4.2% (w/w) in the dry drug. Conclusions: For the first time, two main flavonoids present in R. rosea were quantified systematically. Rhodiosin and herbacetin can be detected simultaneously to phenylpropenoids or salidroside in authentic samples, influenced by the plant part examined and the plant origin. Rhodiosin and herbacetin may serve as additional marker to guarantee a consistent content of R. rosea products.